STUDI FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEMISKINAN DI DESA BORO-BORO KECAMATAN RANOMEETO KABUPATEN KONAWE SELATAN - Muh Festuka Islambay; Hasan Aedy; La Tondi La Tondi (Universitas Halu Oleo, 2017)
The purpose of this research is determine the factors affecting poverty in Boro-Boro Village, Ranomeeto Subdistrict, South Konawe District. The method of analysis that uses is qualitative descriptive in the form of primary data obtained from the results of questionnaires and interviews with respondents. The results of the study show that the factors that influence the level of poverty in the Boro-Boro Village are: 1) Lack of ownership of production factors, namely 67,5 percent did not own land, 97,5 percent did not have capital and 77,5 percent did not have expertise; 2) Low education,, that is equal to 50 percent of respondents only attend school at the elementary level; 3) Low productivity, respondents income 80 percent are in the low to moderate income level with a large number of dependents; 4) Poor view of live, 57,5 percent of respondents did not have aspirations and business, so the respondents preferred to surrender and accept no. Boro-Boro Village are included in the types of cultural and structural poverty.e